THE MAIN WAYS OF FORMING LEXICAL UNITS IN THE FIELD OF INTERNATIONAL LAW IN THE ENGLISH LANGUAGE - Isanova Feruza Tulkinovna (Western European Studies, 2024)
This article examines the main ways of forming lexical units in the field of international law in English. The author also substantiates a number of starting points that determine the content of the academic discipline for law students English in jurisprudence
Keywords: jurisprudence; legal language; legal linguistics